Less‐Energy Consumed Hydrogen Evolution Coupled with Electrocatalytic Removal of Ethanolamine Pollutant in Saline Water over Ni@Ni3S2/CNT Nano‐Heterostructured Electrocatalysts (Small Methods 3/2022). Issue 3 (21st March 2022) - Zhao, Bin; Liu, Jianwen; Feng, Renfei; Wang, Lei; Zhang, Jiujun; Luo, Jing‐Li; Fu, Xian‐Zhu
Abstract : Back Cover In article number 2101195, Fu and co‐workers developed an effective countermeasure for both energy and environmental challenges by integrating electro‐oxidation removal of organic pollutants with energy‐efficient hydrogen production in saline water. The as‐synthesized core/shell Ni@Ni3 S2 /carbon nanotubes nano‐heterostructures are competent for stably electro‐oxidizing ethanolamine pollutant in saline water at the anode with long‐term working stability at high current densities, which not only suppresses oxygen/chlorine evolution reactions but also decreases the energy cost to boost hydrogen production.